Mobile disruption : - Funk, Jeffrey L. (Wiley, 2004)
A disruptive technology is a technology or innovation that results in worse product performance different from the expected or predicted performance; an example is that the Internet accessible mobile phone was thought to be a portable substitute for the PC-the actual applications of mobile phones are far different from this. Describes business models, user needs, and key technologies to create long-term strategies that are profitable in both the long- and short-term